The Law as a Drawbar, or Judicial Arbitrariness: Recidivism = Repetition of Crimes in the Framework of Circumstances Aggravating the Punishment (Law and Safety, 2019)
The author has studied the current problem in Ukrainian criminal law – the problem of the courts’ understanding of the general jurisdiction of the repetition of offences, as well as their recidivism in the framework of the circumstances aggravating criminal punishment. Attention at the beginning of the paper, has been paid to the importance of understanding the regulatory act as the main source of criminal law in Ukraine. It has been demonstrated that it is the regulatory act that should determine the rules, which should be obeyed by the judicial authorities of Ukraine. It has been emphasized that it is necessary to take into account the law while interpreting the prescriptions of normative acts by the national courts; it has been stressed that such interpretation should proceed from the definitions and formulations available, first of all, in the legislation. The author has emphasized on the importance of adhering to the rules and regulations, in the course of such interpretation, used in the law without such unreasonable extension or distortion of their content by relevant court decisions.Having analyzed the relevant Resolution of the Plenum of the Supreme Court of Ukraine, as well as the verdict of one of the Courts of Appeal of Ukraine, the author tries to prove that the aforementioned courts violated the limits of its interpretation in explaining the provisions of the criminal law on repetition of offences and recidivism, while unjustifiably giving the value of one criminal feature to another one. According to the author, these judicial authorities have formally taken the formulation of the content of the repetition of offences and recidivism, which are legally saturated in the current Criminal Code of Ukraine. Thus, they actually ignored the increased public risk of recidivism against the backdrop of the repetition of offences. The specificity of committing the offenses inherent to the recidivism is not taken into account, when a person has already a previous conviction for unlawful activity, as well as the fact that such crimes are usually characterized in terms of their consistency and randomness.On this basis, the author has substantiated the incorrectness (criminal injustice) of the approach recommended by the Plenum of the Supreme Court of Ukraine to the application of the institutions of recidivism and the repetition of offences in deciding the issue of punishment. Proper arguments have been provided. Specific conclusions have been formulated.
Keywords: repetition of offences; recidivism; judicial precedent; regulatory act; criminal law